Abundance of macrozoobenthos in relation to bottom soil textural types and water depth In aquaculture ponds - Nupur, N; Shahjahan, M; Rahman, MS; Fatema, MK (International Journal of Agricultural Research, Innovation and Technology, 2014)
The present experiment was conducted to evaluate the effects of bottom soil textural classes and different water depths on abundance of macrozoobenthos in aquaculture ponds. Three treatments, i.e., ponds bottom with sandy loam (T1), with loam (TS2) and with clay loam (T3) were considered in this experiment. Samples were collected from three different depths (60.96 cm, 106.68 cm and 152.40 cm) with three replications. The ranges of water quality parameters were suitable for the growth of macrozoobenthos during the experimental period. Similarly, chemical properties of soil were also within suitable ranges and every parameter showed comparatively higher ranges in T2. Eight genera were recorded belonging to major groups of Chironomidae, Oligochaeta, Mollusca and Ceratoponogonidae. The highest population densities of Oligochaeta (1200±4.25 per m2), Chironomidae (1422±4.88 per m2), Ceratopogonidae (399±1.56 per m2) and Mollusca (977±2.24 per m2) were found in T2. The population densities of macrozoobenthos showed fortnightly variations in all the treatments. Among the three depths, significantly highest densities of macrozoobenthos were recorded in 106.68 cm in every treatment. The mean abundance of macrozoobenthos was significantly highest in T2. The present study indicates that loamy soil pond bottom along with water depth 106.68 cm is suitable for the growth and production of macrozoobenthos in aquaculture ponds. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17811 Int. J. Agril. Res. Innov. & Tech. 3 (2): 1-6, December, 2013